Early-age heat exposure improved growth performance and heat tolerance in broilers - Y.S. Liu; T.J. Lv; H. Lin; H.C. Jiao; X.J. Wang; L. Liu (Poultry Science)
ABSTRACT: A total of 440 one-day-old healthy male Arbor Acres broilers were equally assigned to a control group (CTL) and an early-age high-temperature exposure (EHT) group (4 replicates per group, 55 chickens per replicate). At d 3, the broilers in CTL group were reared in the normal temperature 33 ± 1°C, while the broilers in EHT group were exposed to 36 ± 1°C for 24 h. At d 43, all broilers were treated with an acute high temperature 35 ± 1°C for 5 h. The results showed that average daily gain in EHT group was decreased at d 3, but average daily gain in EHT group was increased at d 36 to 42 (P < 0.05). Plasma GLU level in EHT group was lower in broilers at d 7 or facing subsequently high temperature for 5 h (P < 0.05). The relative expression of myogenic differentiation (MyoD) gene in pectoralis major and myogenic factor 5 (Myf5) gene in biceps femoris were significantly improved at d 42 after early-age heat exposure (P < 0.05). Broilers in EHT group have a higher temperature tolerance with a lower mortality than control broilers (P < 0.05). Broilers in EHT group have a lower rectal temperature and a higher comb and ear temperature when facing subsequently acute high temperature than control broilers (P < 0.05). In addition, our study demonstrated that early-age heat exposure significantly decreased the mortality and increased the heat tolerance of broilers when facing an acute short-term heat exposures. Early-age heat exposure increased the process of myogenesis via up-regulating the MyoD and Myf5 gene expression in skeletal muscle, which accelerated average daily gain.